If x # y = 3x² – y and x @ y = x + 2y, which of the following is equal to 2x # (2x @ y)?
A. 2x² + 8xy + 4y² B. x² + 8x – 4y C. 10x² – 8 – 4y D. 8x² – 4y² E. 12x² – 2x – 2y
(E) Recall from the rules of order of operations (PEMDAS), that we always work with what is in parenthesis first. Essentially, we want to work from the inside out with this problem.
2x # (2x @ y) = 2x # (2x + 2y) = 3(2x)² – (2x + 2y) = 12x² – 2x – 2y.
The correct answer is E. 
How do you derive "12x²..." in answer choice E? Shouldn't it be "6x²..."?
